Optimalisasi Legal Drafting Dalam Mencegah Tumpang Tindih Peraturan Optimizing Legal Drafting To Prevent Overlapping Regulations - Sri Mahliati; Siti Hafizah; Nor Kamalia; Ahmad Zaki Yamani (Sharia Journal and Education Center Publishing, 2025)
Regional governments in Indonesia play a strategic role in promoting public welfare through the implementation of regional autonomy, one aspect of which is the authority to formulate regional regulations (perda). However, in practice, the process of drafting these regulations often faces various challenges, such as overlapping regulations, weak inter-agency coordination, and limited capacity of regulatory drafters. This study aims to explain the concept of legal drafting, its scope within the formation of legislation, and to analyze the challenges faced in the modern era marked by technological advancements and the increasing complexity of legal issues. The method used is descriptive research with a qualitative approach through literature review. The findings indicate that optimizing legal drafting is essential to improve the quality of regional regulations, prevent normative conflicts, and ensure legal certainty and justice. Systematic, locally relevant legal drafting strengthens regulatory effectiveness. Emphasis is also placed on the importance of collaboration among stakeholders—legislative, executive, and the public—to ensure that regulations reflect public interests. In addition, the use of information technology supports faster data access, regulatory harmonization, and enhanced transparency and accountability. A professional approach, supported by technology and inter-agency coordination, is key to producing responsive regulations that address social dynamics and legal challenges.